Correlation between class participation and motivation on students' English achievement at SMA Negeri 12 Padang, Kec Nanggalo of west Sumatera - Syaveny, Niza; Johari, Indra (Journal Of Language Education and Development (JLed), 2019)
This study aims to determine the relationship of class participation (X1) and motivation (X2) on English learning achievement (Y) of Senior High School number 12 Padang. The population of this research was students of Senior High School number 12 Padang with total population was 894 students. Sample was selected by stratified random sampling technique with total sample was 100 students. The data were collected by using observation and questionnaire. The data were analysis by using quantitative descriptive technique with SPSS computer program version 20. Based on result of data analysis it can be found that first there is positive correlation between X1 with Y with high category (0,793) and significance value less than 0,05 (0,000 <0,05 ), secondly there is a positive correlation between X1 and Y high category (0,783) and significance value less than 0,05 (0,000 <0,05), third there is positive correlation between X1 and X2 on Y with rcount is 0,849 and rtable is 0,163 at significance level 5% and n = 100. It means the higher participation and motivation make learning achievement better. Thus, participation and motivation should be a good consideration in leaning.